Investigating the electric vehicle adoption initiatives for achieving sustainable development goals - Shashi Kant Tripathi; Ravi Kant; Ravi Shankar (Sustainable Futures)
The present study aims to prioritize the electric vehicle adoption initiatives (EVAIs) for achieving the sustainable development goals (SDGs), considering India's EV sector as a case study. A novel research framework of sentence boundary extraction, a machine learning approach, and multi-criteria decision-making is proposed to achieve the research objective. The findings of the study highlight the top two key initiatives, namely, subsidizing solar-powered EV charging, and offering government incentives for EV production and purchases. Further, the EVAIs identified in this study support developing nations in achieving the most important SDGs, namely, affordable and sustainable transportation (SDG11.2), enhanced policy coherence (SDG17.14), and boosting the share of renewable energy (SDG7.2). The study offers actionable insights for EV stakeholders to advance a sustainable future.